2023
DOI: 10.3390/cryst13111585
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescent and Dosimetric Properties of Zirconium Dioxide Ceramics Irradiated with High Doses of Pulsed Electron Beam

Sergey Nikiforov,
Alma Dauletbekova,
Maksim Gerasimov
et al.

Abstract: Thermoluminescent (TL) properties of monoclinic zirconium dioxide ceramics were studied in order to assess the possibility of their use for measuring high doses (on the order of kGy) of pulsed electron beams (130 keV). Two types of samples were used: those synthesized by sintering in an electric furnace at T = 700–1700 °C and those synthesized in a flow of high-energy electrons (1.4 MeV) with a high power density. Analysis of the X-ray diffraction patterns using the Scherrer method revealed that annealing of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The same research group also found that stabilized tetragonal track regions are induced in a monoclinic matrix of natural zirconia by a single SHI impact [33]. Phase transformation in monoclinic zirconia irradiated with SHIs has been extensively investigated [34][35][36][37][38][39][40]. Therefore, monoclinic zirconia can be an intriguing material for investigating the mechanism of SHI-induced melting and recrystallization processes.…”
Section: Introductionmentioning
confidence: 98%
“…The same research group also found that stabilized tetragonal track regions are induced in a monoclinic matrix of natural zirconia by a single SHI impact [33]. Phase transformation in monoclinic zirconia irradiated with SHIs has been extensively investigated [34][35][36][37][38][39][40]. Therefore, monoclinic zirconia can be an intriguing material for investigating the mechanism of SHI-induced melting and recrystallization processes.…”
Section: Introductionmentioning
confidence: 98%